Operationalization SECI Model of Knowledge Management by Enterprise Ontology - Jan Andreasik (Barometr Regionalny)
The paper contains the proposition of solving the problem of operationalization of the SECI model of knowledge creation in a new scope — i.e., in relation to knowledge about managing an SME enterprise in conditions of uncertainty. This knowledge includes the assessment of the enterprise in the potential — risk space of operational activity. This problem was solved theoretically by developing the original A–E–AE enterprise ontology and practically by constructing the SOK-P1 system, which was used in the advisory practice for SME sector enterprises in the Lubelskie and Podkarpackie voivodships.